2015
DOI: 10.1128/jb.02414-14
|View full text |Cite
|
Sign up to set email alerts
|

Revisiting the Gram-Negative Lipoprotein Paradigm

Abstract: The processing of lipoproteins (Lpps) in Gram-negative bacteria is generally considered an essential pathway. Mature lipoproteins in these bacteria are triacylated, with the final fatty acid addition performed by Lnt, an apolipoprotein N-acyltransferase. The mature lipoproteins are then sorted by the Lol system, with most Lpps inserted into the outer membrane (OM). We demonstrate here that the lnt gene is not essential to the Gram-negative pathogen Francisella tularensis subsp. tularensis strain Schu or to the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

6
79
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 61 publications
(85 citation statements)
references
References 58 publications
6
79
0
Order By: Relevance
“…LoVullo and colleagues confirmed this by constructing ⌬lnt deletion mutations in two different F. tularensis strains, including a human-pathogenic F. tularensis subsp. tular-ensis strain (5). The study further demonstrated that the known F. tularensis lipoprotein Tul4 (LpnA) shifts from a triacylated form in the wild-type strain to a diacylated form in the ⌬lnt background and that Tul4 and additional lipoproteins are still properly sorted to the OM in the ⌬lnt mutant.…”
mentioning
confidence: 67%
See 3 more Smart Citations
“…LoVullo and colleagues confirmed this by constructing ⌬lnt deletion mutations in two different F. tularensis strains, including a human-pathogenic F. tularensis subsp. tular-ensis strain (5). The study further demonstrated that the known F. tularensis lipoprotein Tul4 (LpnA) shifts from a triacylated form in the wild-type strain to a diacylated form in the ⌬lnt background and that Tul4 and additional lipoproteins are still properly sorted to the OM in the ⌬lnt mutant.…”
mentioning
confidence: 67%
“…Interestingly, the Lol system of F. tularensis lacks a gene for LolE, which in E. coli heterodimerizes with LolC to form the membrane component of the ABC transporter complex. Comparison of the lol genes present in various Gram-negative bacteria revealed that the absence of lolE is not unique to Francisella, but instead was found in more than half of the bacterial genomes they analyzed (5). Based on protein sequence analysis, LoVullo et al concluded that the single LolC present in bacteria such as Francisella spp.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…42 It is also possible that the presence of LolE permease, part of ABC transporter LolCDE, on E. coli contributed to resistance to this set of compounds, while the other Gram-negative F. tularensis was greatly inhibited. 43 In support of this, one group examining SMIs opted to use a strain of E. coli that has a shortened LPS, which renders it more permeable to SMIs. 44 This technique will be worth considering in future studies.…”
Section: Discussionmentioning
confidence: 99%